Evaluation of various membrane filtration modules for the treatment of seawater - Hisham A. Maddah; Abdulazez S. Alzhrani; M. Bassyouni; M. H. Abdel-Aziz; Mohamed Zoromba; Ahmed M. Almalki (Applied Water Science, 2018)
Abstract This study was initiated to identify the treatment efficiency of various membrane filtration modules in the treatment of Red Sea water at Rabigh City. Filtration efficiency (membrane performance) was calculated in terms of water conductivities of feed and product. Four commercial membranes were utilized in the experiment work and they were Polyvinylidene difluoride (FP100), Polyethersulphone (ES404), Polyamide low-pressure film (AFC40) and Polyamide high-pressure film (AFC99). Different pressure values were applied on each membrane type to determine the optimal operating pressure for the treatment. pH levels of produced water were analyzed relative to feed water pH to check the effect of different applied pressures on pH variations. A comparison between the four membranes was established to select the ideal membrane for the treatment. Results showed that the optimal operating pressures for the four membranes FP100, ES404, AFC40 and AFC99 were 10, 30, 60 and 64 bar, respectively. In general, applying higher pressures would increase the treatment efficiency. An inverse relationship between water conductivity and applied pressure was noted, and pH levels slightly decreased at high pressures. Among the four selected membranes, AFC40 was the ideal choice for water treatment due to its relatively lower energy demand and higher treatment efficiency of 99.9%.